Penguasaan Kosakata Bahasa Inggris Dalam Praktik Front Office - Hana Yulinda Fithriyani; Puput Dewi Anggraeni (Jurnal Pendidikan Indonesia (JOUPI), 2023)
Mastery of vocabulary in the field of hospitality is needed by students as initial capital for them to support them in carrying out speaking practices. The research problem focused on vocabulary mastery of tourism vocational school students in Tegal in front office practice (FO). The research aimed to analyze students’ FO vocabulary mastery and students' strategies to improve FO vocabulary mastery. The research method used descriptive quantitative. The subject in this research were students majoring in hospitality at tourism vocational schools in Tegal. The results showed that 35,5% of respondents scored above 70, 30,3% scored 60-69 and 34,2% of respondents scored below 60, with an overall average score of 62,6. Moreover, Regular Reading, Asking Teacher, Group Discussion, Synonym/Antonym, Using Audio-visual Media, Memorization, and Translation of Literary Passages are ways that many respondents agree on to improve English vocabulary mastery.